On the Reliability of Half-Cell Tests for Monovalent (Li+, Na+) and Divalent (Mg2+, Ca2+) Cation Based Batteries. Issue 7 (2nd May 2017) - Tchitchekova, D. S.; Monti, D.; Johansson, P.; Bardé, F.; Randon-Vitanova, A.; Palacín, M. R.; Ponrouch, A.
Abstract : A comprehensive study is reported entailing a comparison of Li, Na, K, Mg, and Ca based electrolytes and an investigation of the reliability of electrochemical tests using half-cells. Ionic conductivity, viscosity, and Raman spectroscopy results point to the cation-solvent interaction to follow the polarizing power of the cations, i.e. Mg 2+ > Ca 2+ > Li + > Na + > K + and to divalent cation based electrolytes having stronger tendency to form ion pairs – lowering the cation accessibility and mobility. Both increased temperature and the use of anions with delocalized negative charge, such as TFSI, are effective in mitigating this issue. Another factor impeding the divalent cations mobility is the larger solvation shells, as compared to those of monovalent cations, that in conjunction with stronger solvent - cation interactions contribute to slower charge transfer and ultimately a large impedance of Mg and Ca electrodes. An important consequence is the non-reliability of the pseudo-reference electrodes as these present both significant potential shifts as well as unstable behaviors. Finally, experimental protocols in order to achieve consistent results when using half-cell set-ups are proposed.